A novel additive manufactured three-dimensional piezoelectric transducer: Systematic modeling and experimental validation. (1st January 2019) - Wang, Liang; Hofmann, Viktor; Bai, Fushi; Jin, Jiamei; Twiefel, Jens
Highlights: A novel 3D sandwiched piezoelectric transducer with multi contact areas is proposed. The three-dimensional coupling part is printed by laser additive manufacturing. An analytical model is created for the transducer using the transfer matrix method. The feasibility of the transfer matrix model is experimentally validated. Abstract: Sandwich piezoelectric transducers are widely used in many industrial applications due to their attractive advantages of compact structure, no electromagnetic interference, and excellent output performance. V-shaped piezoelectric transducers, a typical design, have been adopted as the stator of ultrasonic motors and the machining tool of elliptical vibration surface manufacturing. However, traditional V-shaped piezoelectric transducers were designed with one contact interface to output effective vibration, limiting their applications. To achieve multi contact areas with synchronous actuation function, a novel three-dimensional sandwich piezoelectric transducer is proposed in this study, expecting to drive wheels of a robotic mobile system. Two orthogonal Langevin transducers are adopted to vertically couple in a cylinder, producing two bending vibrations with a spatial phase difference of π/2 in the cylinder. Therefore, elliptical motion is generated at surface points of two driving parts placed at both ends of the cylinder. Due to the fact that two front-end blocks of the two Langevin transducers and the cylinder form a three-dimensional configuration which hard to be manufactured by traditional machining methods, this part is printed using laser additive manufacturing. To analyze the dynamic behavior of the proposed three-dimensional transducer, an analytical model is carried out utilizing the transfer matrix method for providing systematic modeling. This developed transfer matrix model is not only capable of greatly reducing computation efforts, and it is maybe suitable for the analysis of traditional V-shaped transducers. To validate this developed transfer matrix model and confirm the feasibility of the transducer design, experimental investigations are conducted to measure the vibration characteristics of the proposed transducer prototype using a 3D laser Doppler vibrometer and are compared to the calculation results. The measured and computed resonant frequencies of the transducer are 19.975 kHz and 20.045 kHz for the symmetrical vibration mode, and 20.07 kHz and 20.06 kHz for the anti-symmetrical vibration mode, respectively. Comparisons show that calculation results match well with the experimental results, demonstrating the effectiveness of the developed transfer matrix model and the feasibility of the three-dimensional transducer design.